Retraction notice to “Analysis of Conocurvone, Ganoderic acid A and Oleuropein molecules against the main protease molecule of COVID-19 by in silico approaches: Molecular dynamics docking studies” [Engineering Analysis with Boundary Elements volume 150 (2023) Pages 583-598, (S0955799723001005), (10.1016/j.enganabound.2023.02.043)] - Le, Quynh Hoang; Far, Bahareh Farasati; Mohammad Sajadi, S.; Jahromi, Bahar Saadaie; Kaspour, Sogand; Cakir, Bilal; İnç, Mustafa (Elsevier Ltd, 2023)
This article has been retracted: please see Elsevier Policy on Article Withdrawal (https://www.elsevier.com/about/policies/article-withdrawal). This article has been retracted at the request of the Editor-in-Chief. Post publication, the editors discovered suspicious changes in authorship between the original submission and the revised version, in which two (2) authors were removed from the paper and four (4) new authors (Quynh Hoang Le, Bahar Saadaie Jahromi, Sogand Kaspour, Zahra Abdelmalek), were added, among which was a new first author. The editor investigated further and found that the explanation provided by the authors was deemed unsatisfactory. The editor therefore feels that the findings of the manuscript cannot be relied upon and that the article needs to be retracted. © 2023 Elsevier Ltd